2021
DOI: 10.1080/08927022.2021.1873321
|View full text |Cite
|
Sign up to set email alerts
|

In silico study of the interactions of Pilocarpus microphyllus imidazolic alkaloids with the main protease (Mpro) of SARS-CoV-2

Abstract: The disease outbreak caused by SARS-CoV-2 continues to rise worldwide, even in countries which have considered it controlled. As new cases appear daily, infecting millions of people and causing thousands of deaths, the current in silico study aims to investigate the imidazolic alkaloids of the species Pilocarpus microphyllus (Jaborandi) as a potential inhibitory activity against the M pro protease from SARS-CoV-2, since it plays a fundamental role in the processing of polyproteins that are translated from vira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…Yadav et al suggested the higher reactivity of favipiravir toward Mpro since the presence of electron donor and receptor groups in favipiravir displayed the capability of forming a complex with the external target molecule. Other similar studies include refs and . DFT calculations by Aitouna et al , indicated the epoxidation reaction of parthenolide and himachalene derivatives presented high chemoselectivity.…”
Section: Methods and Approachesmentioning
confidence: 83%
See 1 more Smart Citation
“…Yadav et al suggested the higher reactivity of favipiravir toward Mpro since the presence of electron donor and receptor groups in favipiravir displayed the capability of forming a complex with the external target molecule. Other similar studies include refs and . DFT calculations by Aitouna et al , indicated the epoxidation reaction of parthenolide and himachalene derivatives presented high chemoselectivity.…”
Section: Methods and Approachesmentioning
confidence: 83%
“…Among them, the best one was bisoctrizole . Additionally, some diaminobenzophenone derivatives, prototypical-ketoamide inhibitors, HIV protease inhibitors, leucoefdin, nutraceuticals, and others were also studied. ,,,, Notably, Mohammad et al optimized some complexes of Mpro with ligands in the protein data bank (PDB) and rescored them by AutoDock Vina, with the best PDB structure being 6M2N.…”
Section: Methods and Approachesmentioning
confidence: 99%
“…Noscapine, leuconicine F, nigellidine, epiisopiloturine, camptothecin, anisotine, norboldine were also analyzed through molecular docking for Mpro target (de Sá et al, 2021 ; Devasia et al, 2021 ; Firdiana et al, 2021 ; Ghosh, Chakraborty, Biswas, & Chowdhuri, 2020 ; Jade et al, 2021 ; D. Kumar, Kumari et al, 2020 ; N. Kumar, Sood, van der Spek, Sharma, & Chandra, 2020 ; Maiti et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Also, in another study on Pilocarpus microphyllus alkaloids (Rutaceae), epiisopiloturine showed a suitable interaction with Mpro (−7.0 kcal/mol). Nevertheless, this imidazolic alkaloid was detected as a mutagenic compound in the analysis of ADMET parameters (Ames test) [ 90 ].…”
Section: Alkaloids As Potential Phytochemicals Against Sars-cov-2mentioning
confidence: 99%